Characterization of soil salinization and its driving factors in a typical irrigation area of Northwest China - Zhang, Yuting; Hou, Kai; Qian, Hui; Gao, Yanyan; Fang, Yuan; Xiao, Shan; Tang, Shunqi; Zhang, Qiying; Qu, Wengang; Ren, Wenhao (The Science of the total environment, 2022)
Salinization of irrigation areas is a global environmental challenge. The uncertainty in the distribution of salinization is increased by the complexity of the natural environment. This study adopted Yinchuan Plain as a typical irrigation area to study the relationship between soil salinity and the environment from the perspective of macro-environmental elements and micro-ion composition. A Geographic Weighted Regression model (GWR) was used to predict the risk of salinization in the Yinchuan Plain. The results showed obvious spatial variation in soil salinization in the Yinchuan Plain. Farmland accounted for the largest proportion of salinized land area, followed by woodland and “other” land use categories. The main characteristic ions in the salinized area of the Yinchuan Plain were SO42−, K++Na+and Cl−. The rank of ions in terms of change rate with increasing soil salinity was: SO42− > K+ + Na+ > Cl− > Ca2+ > HCO3− > Mg2+ > CO32−. However, the rank of ions in terms of their sensitivity to salinization was: HCO3− > Ca2+ > Mg2+ > SO42− > Cl− > K+ + Na+. On this basis, the geographical indicators of DEM and NDVI, groundwater indicators of groundwater depth and TDS, climate indicators of SPEI, as well as soil indicators of PH and organic matter were taken as the representative ecological drivers of salinization in irrigation areas. These environmental factors were found to control the distribution of salinization, whereas human activity affected the degree of change in salinization. The enrichment of SO42− in the Yinchuan Plain was mainly related to agricultural activities (such as pesticides application and irrigation evaporation), and followed by phreatic evaporation. The salt ions carried by irrigation and rainfall further polluted phreatic water. In the end, the measures of optimizing drainage, combined irrigation, and improving planting layout were recommended for the effectively and economically controlling of salinization. [Display omitted] •Interpret the process of soil salinization from the perspective of macro-environmental factors and micro-ion compositions•The representative ecological driving factors of salinization in irrigation areas were proposed•A suitable scheme for regulating soil salinization in irrigation areas was provided